Beyond the “3 Ps”: A critical appraisal of the non-endocrine manifestations of multiple endocrine neoplasia type 1 - Waguespack, Steven G. (Frontiers in Endocrinology, 2022)
Multiple endocrine neoplasia type 1 (MEN1), an autosomal-dominantly inherited tumor syndrome, is classically defined by tumors arising from the “3 Ps”: Parathyroids, Pituitary, and the endocrine Pancreas. From its earliest descriptions, MEN1 has been associated with other endocrine and non-endocrine neoplastic manifestations. High quality evidence supports a direct association between pathogenic MEN1 variants and neoplasms of the skin (angiofibromas and collagenomas), adipose tissue (lipomas and hibernomas), and smooth muscle (leiomyomas). Although CNS tumors, melanoma, and, most recently, breast cancer have been reported as MEN1 clinical manifestations, the published evidence to date is not yet sufficient to establish causality. Well-designed, multicenter prospective studies will help us to understand better the relationship of these tumors to MEN1, in addition to verifying the true prevalence and penetrance of the well-documented neoplastic associations. Nevertheless, patients affected by MEN1 should be aware of these non-endocrine manifestations, and providers should be encouraged always to think beyond the “3 Ps” when treating an MEN1 patient.